Digital Public Relations Raspati Management di Tengah Pandemi Covid-19 - indah novianti; Dadi Ahmadi (UNISBA Press, 2022)
Abstract. Raspati Management is an entertainment management that presents many productions in the entertainment field, founded on the basis of a love for the art of music and accompanied by a high sense of social awareness. In Raspati Management there is an event organizer or commonly called EO such as making music events, Expo, Exhibitionx, productions houses, talents/artists. This research is entitled